A universally conserved residue in the SUR1 subunit of the K ATP channel is essential for translating nucleotide binding at SUR1 into channel opening - de Wet, H; Shimomura, K; Aittoniemi, J; Ahmad, N; Lafond, M; Sansom, MS; Ashcroft, F (2012)
The sulphonylurea receptor (SUR1) subunit of the ATP-sensitive potassium (K ATP) channel is a member of the ATP-binding cassette (ABC) protein family. Binding of MgADP to nucleotide-binding domain 2 (NBD2) is critical for channel activation. We identified a residue in NBD2 (G1401) that is fully conserved among ABC proteins and whose functional importance is unknown. Homology modelling places G1401 on the outer surface of the protein, distant from the nucleotide-binding site. The ATPase activity of purified SUR1-NBD2-G1410R (bound to maltose-binding protein) was slightly inhibited when compared to the wild-type protein, but its inhibition by MgADP was unchanged, indicating that MgADP binding is not altered. However, MgADP activation of channel activity was abolished. This implies that the G1401R mutation impairs the mechanism by which MgADP binding to NBD2 is translated into opening of the K ATP channel pore. The location of G1401 would be consistent with interaction of this residue with the pore-forming Kir6.2 subunit. Channel activity in the presence of MgATP reflects the balance between the stimulatory (at SUR1) and inhibitory (at Kir6.2) effects of nucleotides. Mutant channels were 2.5-fold less sensitive to MgATP inhibition and not activated by MgATP. This suggests that ATP block of the channel is reduced by the SUR1 mutation. Interestingly, this effect was dependent on the functional integrity of the NBDs. These results therefore suggest that SUR1 modulates both nucleotide inhibition and activation of the K ATP channel. © 2012 The Authors. The Journal of Physiology © 2012 The Physiological Society.